2020
DOI: 10.1177/1756287220927994
|View full text |Cite
|
Sign up to set email alerts
|

The effects of docetaxel and/or captopril in expression of TGF-β1, MMP-1, CTGF, and PAI-1 as markers of anterior urethral stricture in an animal model

Abstract: Background: Treatment of urethral trauma is currently done after urethral stricture occurs. Stricture therapy after occurrence gives unsatisfactory success rates. Several genes, such as transforming growth factor beta 1 (TGF-β1), matrix metalloproteinase 1 (MMP-1), connective tissue growth factor (CTGF), and plasminogen activator inhibitor 1 (PAI-1), have a proven role in urethral stricture development. The purpose of this study was to assess the effect docetaxel and/or captopril on the RNA expression of those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Docetaxel is a microtubulestabilizing taxane, and it has increased a nity for tubulin [34]. This drug suppresses the expression of TGF-β, as does paclitaxel [35]. Therefore, it is thought that docetaxel may inhibit the function of broblasts and brocytes that are associated with stromal brosis in cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel is a microtubulestabilizing taxane, and it has increased a nity for tubulin [34]. This drug suppresses the expression of TGF-β, as does paclitaxel [35]. Therefore, it is thought that docetaxel may inhibit the function of broblasts and brocytes that are associated with stromal brosis in cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Kurniawan et al . 139 revealed that captopril alone reduced connective tissue growth factor (CTGF) expression, and the combination of docetaxel and captopril reduced TGF-β1 and CTGF expression. These findings suggest that the effectiveness and efficiency of treatment can be enhanced by inhibiting two different pathways.…”
Section: Obstacles To Medicationmentioning
confidence: 99%